Badanie związków między miarami zróżnicowania błędów pojedynczych modeli a jakością modelu zagregowanego - Rozmus, Dorota (Analysis of relationship between diversity measures and error of aggregated classifier, 2006)
The main aim of ensembles is improvement of their classification and prediction accuracy. One of the elements required for accurate prediction when using an ensemble is recognised to be error „diversity”. The paper presents different diversity measures and disscuss their main properties. It shows also the influence of different factors (eg. number of single models, the training set size) on the diversity of base classifiers of the ensemble.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 214-223